Improving Mathematical Creativity Through Self-Regulated Learning in a Problem-Based Learning Model Supported by GeoGebra - Ernita, Ernita; Isnarto, Isnarto; Suyitno, Amin (Department of Mathematics Education Program IPI Garut, 2024)
Creative thinking is a crucial skill in the 21st century. However, creative thinking abilities are still lacking in Indonesia, with a global creativity index of just 0.202, indicating very low level. This study seeks to evaluate the quality of GeoGebra-assisted Problem-Based Learning in enhancing students' creative thinking skills and to describe students' creative thinking abilities in relation to Self-Regulated Learning. The research method used is a mixed method. The research sample includes students from grades VIII D and VIII E at SMP Negeri 2 Ungaran. The subjects of this study are 6 students categorized by their level of Self-Regulated Learning. Quantitative data analysis involves t-tests and z-tests, qualitative data analysis involves data reduction, presentation, interpretation, and drawing conclusions. The study finds that GeoGebra-assisted Problem-Based Learning effectively enhances creative thinking skills. Students with high, medium, and low Self-Regulated Learning levels showed very good, good, and poor mathematical creative thinking abilities, respectively. Berpikir kreatif merupakan kemampuan yang sangat diperlukan di abad 21. Akan tetapi kemampuan berpikir kreatif masih sangat kurang di Indonesia, ditunjukkan dengan indeks kreativitas global Indonesia yaitu 0,202 yang tergolong sangat rendah. Penelitian ini bertujuan untuk mengetahui kualitas Problem Based Learning berbantuan GeoGebra terhadap peningkatan kemampuan berpikir kreatif siswa dan mendeskripsikan kemampuan berpikir kreatif siswa berdasarkan Self-Regulated Learning. Metode penelitian yang digunakan yaitu mixed method. Sampel penelitian yaitu siswa kelas VIII D dan VIII E SMP Negeri 2 Ungaran. Subjek penelitian yaitu 6 siswa berdasarkan tingkat Self-Regulated Learning. Analisis data kuantitatif menggunakan uji t dan uji z. Analisis data kualitatif mencakup penyederhanaan data, penyajian, interpretasi, dan penarikan kesimpulan. Hasil penelitian mengindikasikan bahwa Problem Based Learning yang didukung GeoGebra berkualitas dalam meningkatkan kemampuan berpikir kreatif serta kemampuan berpikir kreatif matematis siswa dengan tingkat self-regulated learning tinggi, sedang, dan rendah, masing-masing dengan hasil sangat baik, baik, dan kurang.